Analysis Of Patient Safety Culture And Its Impact On Patient Safety Performance (A Study on Nurses’ Perceptions of Patient Safety Culture at Fatmawati Central General Hospital, Jakarta) - Irviana, Fitriyati (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of patient safety culture on patient safety performance at Fatmawati Central General Hospital Jakarta. Patient safety culture is examined through three key dimensions: safety culture at the management level, safety culture at the unit level, and the outcome of safety culture. The research employs a mixed methods approach using a sequential explanatory model, which combines quantitative and qualitative analysis. The quantitative data were collected through a survey involving 83 nurses selected using proportional random sampling. Data analysis was conducted using multiple linear regression with the help of SPSS version 17. In the qualitative phase, in-depth interviews were conducted with selected informants to deepen the understanding of the quantitative findings. The results of the study show that all three independent variables have a significant positive effect on patient safety performance, with significance values below 0.05. The outcome dimension shows the strongest influence, indicating that incident reporting and safety awareness are crucial to improving performance. The coefficient of determination (R²) is 0.424, meaning that 42.4% of the variation in patient safety performance is explained by the model. In conclusion, strengthening patient safety culture—through leadership support, unit-level collaboration, and outcome monitoring—plays a vital role in enhancing patient safety and service quality in hospital environments.